2020
DOI: 10.1159/000509662
|View full text |Cite
|
Sign up to set email alerts
|

Early Prophylactic Enoxaparin for the Prevention of Preeclampsia and Intrauterine Growth Restriction: A Randomized Trial

Abstract: Background: Preeclampsia (PE) and intrauterine growth restriction (IUGR) are major causes of maternal and perinatal morbidity and mortality. Previous studies have shown that intervention with low-dose aspirin resulted in a reduction in the occurrence of preterm PE. However, no data are currently available on the effect of low-molecular-weight heparin (LMWH) for the prevention of pregnancy complications in women enrolled at first trimester screening. Objective: We aimed to assess the effectiveness of LMWH in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…No statistically significant differences were found in terms of the occurrence of HELLP syndrome between LMWH-treated and nontreated patients (8 RCTs, 1243 participants; OR, 0.65; 95% CI, 0.27e1.56; P¼.340; I 2 ¼0%) (Supplemental Figure 8). Notably, 7 RCTs recorded the outcome 22,23,39,42,43,45,49 One study 43 reported 3 episodes of eclampsia, 1 in the LMWH group and 2 in the nontreated group; 3 studies 23,42,48 reported maternal mortality as an outcome, with no events in either group.Adverse events. No statistically significant difference in bleeding was found between LMWH-treated and nontreated patients, regardless of whether or not LMWH was combined with LDA (10 RCTs, 2109 participants; OR, 1.14; 95% CI, 0.75e1.71; P¼.540; I 2 ¼8%) (Figure 9).…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…No statistically significant differences were found in terms of the occurrence of HELLP syndrome between LMWH-treated and nontreated patients (8 RCTs, 1243 participants; OR, 0.65; 95% CI, 0.27e1.56; P¼.340; I 2 ¼0%) (Supplemental Figure 8). Notably, 7 RCTs recorded the outcome 22,23,39,42,43,45,49 One study 43 reported 3 episodes of eclampsia, 1 in the LMWH group and 2 in the nontreated group; 3 studies 23,42,48 reported maternal mortality as an outcome, with no events in either group.Adverse events. No statistically significant difference in bleeding was found between LMWH-treated and nontreated patients, regardless of whether or not LMWH was combined with LDA (10 RCTs, 2109 participants; OR, 1.14; 95% CI, 0.75e1.71; P¼.540; I 2 ¼8%) (Figure 9).…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…With the exception of bleeding and allergies, other adverse effects reported were very rare. Thrombocytopenia was reported in 3 studies, 22,38,42 with a range between 0 and 6 events; thrombosis was reported in 3 studies, 22,38,39 with a range between 0 and 4 events, and finally, another study reported similar numbers of transfusion events in both groups. 42 Uni-vs multicenter studies.…”
Section: Systematic Review Ajogorgmentioning
confidence: 98%
See 2 more Smart Citations
“…The benefits of this standard regime may be largely attributable to LDA since it has been shown to improve gestational complications when used alone in women at risk of pre-eclampsia without ARD, with a reduction in preeclampsia in 53% of cases, IUGR in 56% and preterm birth in 78% of cases (37). Furthermore, a recent randomized trial by Llurba et al (38) found that LMWH in women at high risk of pre-eclampsia without thrombophilia did not reduce placental insufficiency compared with no intervention.…”
Section: Discussionmentioning
confidence: 99%